Honeycomb‐Inspired Heterogeneous Bimetallic Co–Mo Oxide Nanoarchitectures for High‐Rate Electrochemical Lithium Storage. Issue 5 (15th March 2019) - Mei, Jun; Liao, Ting; Spratt, Henry; Ayoko, Godwin A.; Zhao, X. S.; Sun, Ziqi
Abstract: Nanostructure engineering has been proved to be an efficient approach for improving electrochemical properties for energy storage by accommodating volume changes, facilitating rapid mass transport paths, and enlarging ion storage sites and interfaces. The well‐designed fine nanostructures, unfortunately, are usually destroyed during long‐term cycles and ultimately lose their structural advantages. Herein, stimulated by the extraordinary structural stability, robust mechanical properties, and salient ventilation capacity of natural honeycomb species, bioinspired heterogeneous bimetallic Co–Mo oxide (CoMoO x ) nanoarchitectures assembled from 2D nanounits are successfully fabricated via a molybdenum‐mediated self‐assembly strategy for improving the rate capability of electrochemical lithium storage devices. Owing to the robust structural stability and the ultrathin 2D wall structure, CoMoO x nanostructures present well‐maintained honeycomb‐like structure, rapid capacitive insertion–desertion behaviors, and thus significantly enhanced lithium ion storage performance at high rates (5.0 A g −1 ). It is also revealed that the reversible transition of cobalt and molybdenum phases closely associated with the ultrathin 2D wall structures greatly contribute to the outstanding electrochemical lithium storage performances. This attractive integration of structural and functional advantages achieved by learning from nature offers new insights into the design of cost‐effective electrode materials for high‐performance energy devices. Abstract : Bioinspired heterogeneous bimetallic CoMoO x nanoarchitectures assembled from 2D nanounits are successfully fabricated via molybdenum‐mediated self‐assembly approach and their electrochemical lithium storage performances, particularly rate capability, is evidenced as attractive due to the robust structural stability, ultrathin 2D wall structure, and open porous structure with unique bimetallic components contributed by the honeycomb‐inspired CoMoO x structures.